2008
DOI: 10.1063/1.2919523
|View full text |Cite
|
Sign up to set email alerts
|

Three dimensional silicon-air photonic crystals with controlled defects using interference lithography

Abstract: Interference lithography is an attractive technique for the creation of three dimensional photonic crystals. Structures with potential for photonic applications are fabricated in a photoresist through concurrent exposure with four coherent beams of laser radiation. The polymer-air templates are used to create higher refractive index contrast photonic crystals by infilling using atomic layer deposition followed by chemical vapor deposition. These photonic crystals exhibit excellent optical properties with stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 21 publications
1
52
0
Order By: Relevance
“…To fabricate a-Si single gyroid structures, we developed a protocol which incorporates multiple steps 2,12,13,23,24 (see Methods for detailed description), as illustrated in Fig. 2 Table S1 for fill fraction values).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To fabricate a-Si single gyroid structures, we developed a protocol which incorporates multiple steps 2,12,13,23,24 (see Methods for detailed description), as illustrated in Fig. 2 Table S1 for fill fraction values).…”
Section: Resultsmentioning
confidence: 99%
“…Three-dimensional photonic crystals offer opportunities to probe interesting photonic states such as bandgaps [1][2][3][4][5][6][7][8] , Weyl points 9,10 , well-controlled dislocations and defects [11][12][13] . Combinations of morphologies and dielectric constants of materials can be used to achieve desired photonic states.…”
Section: Table Of Contents Graphicmentioning
confidence: 99%
“…Two-photon ablation or polymerization was used to create defects in PhC template in SU-8, which were created through holographic lithography, by three research groups in 2005, 18 2006, 19 and 2008. 20 Sun et al 18 demonstrated the hybrid holographic and direct writing method in a two-dimensionally periodic structure while Scrimgeour et al 19 described the creation of defect structures inside 3D PhCs. The other group 20 fabricated and developed polymer-air PhCs in SU-8 via holographic lithography and the PhCs were infiltrated with trimethylol propane triacrylate and a two-photon sensitive photoinitiator for the direct writing of defects via an ultrafast laser.…”
Section: Photonic Crystals With Defect Structures Fabricated Through mentioning
confidence: 99%
“…Similarly, Figure 6(b) demonstrates a multi-step procedure to create more complex composite patterns. Others have combined MBIL with various lithographic techniques including other mask-based techniques (e.g., proximity or contact lithography) [159,173], electron-beam lithography [81,174,175], electron-beam-induced deposition [176], focused ion-beam lithography [155,177], direct laser writing [77,150,178,179], atomic force microscopy nano-indentation [180], and multi-photon polymerization [181][182][183]. For example, interference lithography has been combined with optical contact lithography to fabricate triple-gate metal-oxide-semiconductor field effect transistors [161].…”
Section: Multi-beam Interference Lithography and Nano-electronicsmentioning
confidence: 99%